Serendipity in biological therapy: a 13-year-old patient with psoriasis and vitiligo treated with etanercept. - Consales, V.; Campanati, A.; Giannoni, M.; Bobyr, I.; Ganzetti, G.; Giuliodori, K.; Offidani, A. (European Journal of Pediatric Dermatology, 2016)
The usefulness of TNF alpha inhibitors for the treatment of psoriasis is well known, while data concerning biologics in vitiligo are discordant. We reported a case of a successful use of etanercept and NB-UVB phototherapy in a 13-year-old girl suffering from psoriasis and vitiligo, and discussed therapeutic results taking into consideration the more recent data of literature on the use of TNF alpha inhibitors in psoriasis and vitiligo.